The sloboda of the stremyannykh streltsy in Moscow. Findings from archaeological excavations - Mojsiejew, Maksim (City and War, 2021)
The article is devoted to the Streltsy Stremyannogo Regiment settlement, located in Moscow near the Kremlin on the right bank of the Neglinnaya River. This settlement was excavated by Moscow archaeologists in the 1990s. Scientists found fragments of urban infrastructure, residential buildings, household items. However, these findings did not become the subject of a special study devoted to the life of the Moscow Streltsy. The proposed study is an attempt at a preliminary study of this problem. The paper gives a brief history of the excavations at Manezhnaya Square in 1993–1997, analyzes the basic historiography devoted to the Streltsy. Archaeological field documentation and albums of finds were used for the study. The analysis of the objects allowed us to conclude that the Stremyany Regiment archers were close to the top of the Moscow urban population.